Rapid ID of diarrhea causing K88 E. coli - Mills, K.W.; Phillips, R.M.; Kelly, B.L.; Baughman, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The efficiency of the standard agglutination test, Y-1 mouse adrenal cell test, and infant-mouse gastric test was compared with a recently developed enzyme-linked immunosorbent assay (ELISA) for detecting the K88 pilus antigen and enterotoxin-producing E. coli. Isolates from clinical samples were identified on suspensions of bacteria. The sensitivity of the assay was in the nanogram-per-ml range as determined by measuring purified pili.
Keywords: Swine; Diarrhea; K88 E. coli